Online Learning lifelong learning: a solution for all? - Alfredo Soeiro (2018)
http://www.qou.edu/home/viewCmsContentDtlEn.do?contentId=58646 On Monday, 30/07/2018, the Continuing Education and Community Service Center at QOU held the first Symposium of Digital Transformation in Continuing Education at the Red Crescent Society headquarter in Al-Bireh. The symposium was held under the auspices of his Excellency Dr. Sabri Saidam, Minister of Education and higher Education and in cooperation with the European Universities Continuing Education Network (EUCEN), with Exclusive sponsorship of JAWWAL.